2012
DOI: 10.1021/ef300714p
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Asphaltene Deposition Tool (ADEPT): Field Application

Abstract: Asphaltenes tend to deposit in reservoir, well tubing, flow lines, separators, etc., causing significant production losses. Asphaltenes are originally stable in crude oil at reservoir conditions. However, changes in temperature, pressure, and/or composition may cause asphaltenes to precipitate and potentially deposit onto the surfaces of a flowing conduit. There are several publications in the literature that discuss modeling of asphaltene phase behavior in oil as well as development of deposition models to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 21 publications
2
61
0
Order By: Relevance
“…Vargas et al [11] proposed a model which simultaneously considered asphaltene precipitation, particle transport, asphaltene aggregation and deposition. Kurup et al [12][13] further simplified the model to one-dimension, and included diffusion due to turbulent velocity fluctuation.…”
Section: Introductionmentioning
confidence: 99%
“…Vargas et al [11] proposed a model which simultaneously considered asphaltene precipitation, particle transport, asphaltene aggregation and deposition. Kurup et al [12][13] further simplified the model to one-dimension, and included diffusion due to turbulent velocity fluctuation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been claimed by different authors that asphaltene deposition in production tubing is driven by Brownian diffusion . A model using this deposition mechanism was developed by Eskin et al and demonstrated reasonably high accuracy in forecasting asphaltene deposit mass in a laboratory Taylor‐Couette (TC) device, in which the inner cylinder rotates and the outer one is immobile.…”
Section: Introduction: Description Of the Asphaltene Deposition Modelmentioning
confidence: 99%
“…When dealing with crude oil fractions, most of the attention is focused on asphaltenes mainly due to its adverse influences on the downstream and upstream sectors of petroleum industry. Asphaltenes are known as the heaviest and the most polar portion of crude oil (Kurup et al 2012) and are defined as fractions of crude oil that are soluble in benzene but insoluble in n-heptane (Shirani et al 2012a, b). Under initial reservoir conditions, asphaltenes are equilibrated in crude oil through peptizing by resins (Kurup et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Asphaltenes are known as the heaviest and the most polar portion of crude oil (Kurup et al 2012) and are defined as fractions of crude oil that are soluble in benzene but insoluble in n-heptane (Shirani et al 2012a, b). Under initial reservoir conditions, asphaltenes are equilibrated in crude oil through peptizing by resins (Kurup et al 2012). With changes in thermodynamic conditions such as pressure, temperature, and crude oil composition, stable dispersion of asphaltenes in crude oil would be destabilized; hence, asphaltenes precipitate out of the crude oil solution and settle in the form of solid deposits which can impede the production process (Shirani et al 2012a, b).…”
Section: Introductionmentioning
confidence: 99%